Transient leukaemia of down syndrome in the Western Cape and outcome of cases at Tygerberg Hospital, South Africa. - Mathure, Muhammad Wakeel (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed)--Stellenbosch University, 2021.